Cherchez... le bruit! Marcel Proust in Service of Modern Communication - Eram, Cosana (InMediaciones de la Comunicación, 2016)
My assumption is that the chasm between inner and outer self is rendered acute in Proust’s notations about domestic and public existence in the modern age, featuring noise as the main intrusive “benefit.” Therefore, two main questions inform this essay: first, what is the relationship between modernization and writerly aesthetic perception? Second, how can this communicative relationship be conceptualized?